2021
DOI: 10.1111/tran.12498
|View full text |Cite
|
Sign up to set email alerts
|

NY‐LON 2020: The changing relations between London and New York in corporate globalisation

Abstract: Studies of cities in globalisation now constitute a large and varied literature on changing urban geographies. It began with Peter Hall's (1966) pioneering study of leading cities of the post-Second World War economic boom. He developed a place-based synthesis of urban characteristics blending to constitute a specific "type" of city: world cities. According to Hall, what set world cities apart was their extensive relationality across borders: in his view and at the time, there was a marked difference between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…In effect, the significance of the energy sector may in fact increase in the future in relation to the C & C function of cities. In addition, the ongoing process of globalization [56] is creating opportunities for development across the energy sectors of developing countries [57].…”
Section: Discussionmentioning
confidence: 99%
“…In effect, the significance of the energy sector may in fact increase in the future in relation to the C & C function of cities. In addition, the ongoing process of globalization [56] is creating opportunities for development across the energy sectors of developing countries [57].…”
Section: Discussionmentioning
confidence: 99%
“…Second, such comprehensive rankings may disguise that different cities perform different roles in the banking sector, which may in turn lead to typologies of banking centers. For example, London's wholesale global city centrality (Taylor and Derudder, 2022) goes hand in hand with a prominent role in a range of specialized banking services. Hall (2017Hall ( , 2021 described the development of offshore RMB markets in its financial district.…”
Section: European Cities As Banking Centers: Processes and Typologiesmentioning
confidence: 99%
“…Finally, although global interconnectedness is more important for GCs than belonging to a given economy (Goerzen et al, 2013) (as shown by the example of London and New York, which do not compete but complement each other, being a conglomerate of transoceanic services facilitating economic globalisation - Taylor & Derudder, 2022), it is difficult to completely exclude the factors of a country or a group of associated countries (e.g., within the European Union, the Eurasian Economic Union, or the North American Free Trade Agreement) for perceiving their attractiveness from the perspective of MNEs.…”
Section: Global Cities' Attractiveness For Mne Operationsmentioning
confidence: 99%